Upregulation of Aedes aegypti Vago1 by Wolbachia and its effect on dengue virus replication. (January 2018) - Asad, Sultan; Parry, Rhys; Asgari, Sassan
Abstract: Dengue infection along with its related disease conditions poses a significant threat to human health. The pathogen responsible for this infection is dengue virus (DENV) which is primarily transmitted to humans through the bites of Aedes aegypti mosquitoes. Unavailability of a potent vaccine has recently sparked renewed research endeavours aimed at vector control. To date, Wolbachia as an endosymbiotic bacterium has shown promise as a novel biocontrol agent to restrict DENV replication in the vector, although the underlying antiviral mechanism remains elusive. Recent studies have demonstrated the potential role of Vago as a novel secretory protein involved in cross-talk between the innate immune pathways in Culex quinquefasciatus mosquitoes to restrict West Nile virus replication. In this study, we have identified two homologs of the Vago protein in Ae. aegypti and looked into their modulation in the case of Wolbachia w MelPop strain infection. Furthermore, we have investigated the role of AeVago1, that is highly induced by Wolbachia, in the context of Wolbachia -mosquito-DENV interactions. Knockdown studies of the AeVago1 gene in Wolbachia -infected cells led to significant increases in DENV replication, with no effect on Wolbachia density. Our results suggest that the Wolbachia -induced AeVago1 in Ae. aegypti may function as a host factor to suppress DENV replication in the mosquito. Graphical abstract: Highlights: Wolbachia induces AeVago1 in young female mosquitoes. Wolbachia -mediated activation of AeVago1 may contribute towards dengue virus (DENV-2) inhibition. AeVago1 has no effect on Wolbachia density.